2014
DOI: 10.1002/2014ja019933
|View full text |Cite
|
Sign up to set email alerts
|

Wide longitudinal distribution of interplanetary electrons following the 7 February 2010 solar event: Observations and transport modeling

Abstract: We analyze 65–105 keV electrons in the 7 February 2010 solar electron event observed simultaneously by STEREO‐A, STEREO‐B, and ACE. A method to reconstruct the full‐electron pitch angle distributions from the four Solar Electron and Proton Telescope sensors on STEREO‐A/B and the Solar Electron and Proton Telescope instrument on ACE in the energy range of approximately 60–300 keV for periods of incomplete angular coverage is presented. A transport modeling based on numerical solutions of a three‐dimensional par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
70
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(78 citation statements)
references
References 62 publications
(92 reference statements)
6
70
2
Order By: Relevance
“…Interestingly, two of the three events that lack a type II radio burst are class (2) events, suggesting that a shock may not be the key ingredient for the wide SEP distribution close to the Sun. This also was the conclusion by Dröge et al (2014), who studied one of these events in detail, that of 7 February 2010, and suggested that the lateral transport of the SEPs in this event occurs partially close to the Sun and partially in the IP medium. Furthermore, all of the events in our sample are accompanied by EIT waves (see Table 1).…”
Section: Discussionsupporting
confidence: 65%
See 2 more Smart Citations
“…Interestingly, two of the three events that lack a type II radio burst are class (2) events, suggesting that a shock may not be the key ingredient for the wide SEP distribution close to the Sun. This also was the conclusion by Dröge et al (2014), who studied one of these events in detail, that of 7 February 2010, and suggested that the lateral transport of the SEPs in this event occurs partially close to the Sun and partially in the IP medium. Furthermore, all of the events in our sample are accompanied by EIT waves (see Table 1).…”
Section: Discussionsupporting
confidence: 65%
“…To investigate the eventto-event variations and the specific dominance of the different mechanisms, detailed modeling of the events is required (e.g. Dröge et al 2010;Kallenrode et al 1992;Dröge et al 2014).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These approaches have support in full-orbit particle simulations (Giacalone and Jokipii, 1999) and galactic cosmic ray observations (Burger et al, 2000;Potgieter et al, 2014). However, several recent observational studies suggest faster propagation of SEPs across the mean field than predicted by the current theoretical understanding: they often require a ratio of the cross-field diffusion coefficient to the parallel one of order k ⊥ /k k ∼ 0.1 À 1 (Zhang et al, 2003;Dresing et al, 2012;Dröge et al, 2014) 1 , whereas values k ⊥ /k k ≲ 0.01 are more consistent with the interplanetary turbulence conditions at 1 AU (Burlaga and Turner, 1976;Pei et al, 2010;Laitinen et al, 2016).…”
Section: Introductionmentioning
confidence: 90%
“…The interpretations offered for such widespread events include: (a) the propagation of CME-driven shocks able to inject SEPs over broad angular regions (Rouillard et al 2012;Lario et al 2016); (b) the effective propagation of particles perpendicular to the direction of the interplanetary magnetic field (IMF), i.e. cross-field diffusion (Dresing et al 2012;Dröge et al 2014); (c) the perpendicular transport of particles through processes other than diffusion (Wiedenbeck et al 2012). Hence, this wealth of observations from different vantage points within the heliosphere has provided significant insight and further tested the proposed mechanisms for the injection, propagation and acceleration of the SEP events.…”
Section: Introductionmentioning
confidence: 99%